2014
DOI: 10.1152/ajpendo.00452.2013
|View full text |Cite
|
Sign up to set email alerts
|

Activation of alternative NF-κB signaling during recovery of disuse-induced loss of muscle oxidative phenotype

Abstract: Remels AH, Pansters NA, Gosker HR, Schols AM, Langen RC. Activation of alternative NF-B signaling during recovery of disuseinduced loss of muscle oxidative phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 47 publications
7
22
0
Order By: Relevance
“…The loss of mitochondrial content and oxidative capacity has been well‐established in different immobilization models in both rat and murine skeletal muscle . More specifically, a decrease in muscle mitochondrial content was reported upon 14 days of UL in the exact same experimental setting as the current murine study, which subsequently recovered during muscle reloading . In line with this, 7 days of strict bedrest, and 14 but not 2 days of human limb immobilization resulted in decreased mitochondrial content markers .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The loss of mitochondrial content and oxidative capacity has been well‐established in different immobilization models in both rat and murine skeletal muscle . More specifically, a decrease in muscle mitochondrial content was reported upon 14 days of UL in the exact same experimental setting as the current murine study, which subsequently recovered during muscle reloading . In line with this, 7 days of strict bedrest, and 14 but not 2 days of human limb immobilization resulted in decreased mitochondrial content markers .…”
Section: Discussionsupporting
confidence: 77%
“…Of interest, mitophagy signaling has not been studied in the early phases of inactivity preceding apparent loss of mitochondrial content. Moreover, many studies have reported expression of mitochondrial dynamics markers in rodent models of muscle inactivity, but convincing evidence indicating increased fission is still lacking . In human studies, it has been shown that expression of key regulators of mitochondrial biogenesis are lower in the skeletal muscle of chronically inactive compared with active subjects, and that transcript abundance of some autophagy‐ and mitophagy‐related markers was lower in inactive subjects .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as expected upon exercise training, C1 displayed an increase in OXCAP markers upon PR, reflecting a restoration of the oxidative metabolic machinery. This is corroborated by the decreased expression of oxidative metabolism regulation markers, as a normalization of metabolism‐related mRNA has previously been shown in late‐stage muscle regeneration . Conversely, in C2, oxidative metabolism regulation and OXCAP were statistically unaltered, although oxidative metabolism regulation seemed to increase upon PR.…”
Section: Discussionsupporting
confidence: 77%
“…Conversely, decreased physical activity results in altered signaling pathways leading to loss of skeletal muscle mass and decreased muscle oxidative metabolism [241244] . PGC-1α is highly responsive to muscle contraction and has been extensively examined for the regulation of oxidative metabolism by physical activity [87,245] .…”
Section: Cancer Cachexia-induced Regulation Of Skeletal Muscle Oximentioning
confidence: 99%